Unique Interactions of Interpersonal Trauma and Positive Peer and Family Experiences on Traumatic Distress Among Pediatric Primary Care Patients - Wang, Shirley B. (Journal of interpersonal violence, 2021)
Individuals with histories of interpersonal trauma are at increased risk for posttraumatic stress disorder (PTSD). Risk of PTSD is particularly salient during critical periods of development, such as adolescence and emerging adulthood. However, little is known about the unique effects and interactions of protective factors and interpersonal trauma on PTSD symptoms in adolescents and young adults. The current study tested whether positive peer and family experiences decrease the associations between interpersonal trauma and PTSD symptoms and whether these associations differed by victim–perpetrator relationships. Participants included 3,618 adolescents and young adults (aged 14-24 years) who completed the Behavioral Health Screen—a web-based screening tool that assesses psychiatric symptoms and associated risk factors—during a routine visit across 10 primary care sites in Pennsylvania. In support of the stress buffering hypothesis, results revealed that positive peer and family experiences buffered the effects of interpersonal trauma by a romantic partner and an adult in the home. Future research should examine whether programs aimed at improving peer or family relationships improve outcomes for traumatized youth.